2000
DOI: 10.1097/00004647-200002000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Cerebral Fractional Oxygen Extraction Using Near Infrared Spectroscopy in Preterm Neonates

Abstract: Cerebral fractional oxygen extraction (FOE) represents the balance between cerebral oxygen delivery and consumption. This study aimed to determine cerebral FOE in preterm infants during hypotension, during moderate anemia, and with changes in the PaCO2. Three groups of neonates were studied: stable control neonates (n = 43), anemic neonates (n = 46), and hypotensive neonates (n = 19). Cerebral FOE was calculated from the arterial oxygen saturation measured by pulse oximetry, and cerebral venous oxygen saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
7
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 56 publications
7
88
7
1
Order By: Relevance
“…This previous study described lower cerebral OEF in a cohort of 11 infants, with two preterm infants having extremely low CMRO 2 and cerebral OEF. The values demonstrated in our study, however, are comparable with more recent studies of cerebral OEF in both preterm infants (Wardle et al, 1998) and in older children undergoing cardiopulmonary bypass (Wardle et al, 2000). The discrepancy between our data and that of Altman et al most probably reflects the differences between the two study populations.…”
Section: Discussionsupporting
confidence: 55%
“…This previous study described lower cerebral OEF in a cohort of 11 infants, with two preterm infants having extremely low CMRO 2 and cerebral OEF. The values demonstrated in our study, however, are comparable with more recent studies of cerebral OEF in both preterm infants (Wardle et al, 1998) and in older children undergoing cardiopulmonary bypass (Wardle et al, 2000). The discrepancy between our data and that of Altman et al most probably reflects the differences between the two study populations.…”
Section: Discussionsupporting
confidence: 55%
“…The Hamamatsu NIRO 500 and a pulse oximeter in beat-to-beat mode (Datex-Ohmeda) with partial jugular venous occlusion was used to measure cerebral venous oxygen saturation (CSvO 2 ). The CSvO 2 value was the mean of five partial jugular venous occlusions made over a 5 to 10 min period and selected using preset criteria (8,18). Cerebral arterial oxygen saturation (CSaO 2 ) was assumed to be equal to peripheral arterial oxygen saturation.…”
Section: Methodsmentioning
confidence: 99%
“…Cerebral arterial oxygen saturation (CSaO 2 ) was assumed to be equal to peripheral arterial oxygen saturation. CFOE was calculated using the formula: CFOE ϭ CSaO 2 -CSvO 2 / CSaO 2 (8,18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusions are limited by the fact that cerebrovascular autoregulation can also be impaired due to illness or therapeutic interventions. Two studies found intact cerebrovascular autoregulation in all of the preterm infants studied, either undergoing high-frequency oscillatory ventilation [26] or treated for hypotension [27]. This was based on the absent relationship between CBF or cerebral fractional oxygen extraction (measured by NIRS) and ABP.…”
Section: Autoregulatory Capacitymentioning
confidence: 99%